2003
DOI: 10.1097/01.aud.0000100206.96363.05
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pseudohypacusis: A Prospective, Randomized Study of the Use of Otoacoustic Emissions

Abstract: The inclusion of TEOAEs and tympanometry in an audiological protocol used in the evaluation of patients suspicious of pseudohypacusis resulted in a significantly greater threshold improvement on repeat modified pure-tone audiometry when compared to the improvement observed for a control group in which these tests were not performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
(25 reference statements)
0
13
2
2
Order By: Relevance
“…Click-evoked ABR thresholds result in reasonable predictions of the average behavioral thresholds at 2 and 4 kHz, thus limiting their utility in patients with NOHL who have underlying high-frequency hearing loss 9 . However, previous studies have reported that ABR thresholds appear to be related most closely to the audiometric thresholds at 2 to 4 kHz, when the best hearing is in this region, and may underestimate the higher frequencies and partially the lower frequencies 3 . In this study, the subjects were initially evaluated with PTA, Stenger test and ART.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…Click-evoked ABR thresholds result in reasonable predictions of the average behavioral thresholds at 2 and 4 kHz, thus limiting their utility in patients with NOHL who have underlying high-frequency hearing loss 9 . However, previous studies have reported that ABR thresholds appear to be related most closely to the audiometric thresholds at 2 to 4 kHz, when the best hearing is in this region, and may underestimate the higher frequencies and partially the lower frequencies 3 . In this study, the subjects were initially evaluated with PTA, Stenger test and ART.…”
mentioning
confidence: 93%
“…Less than 2% of the general population attempt to exaggerate a hearing loss, but the prevalence of NOHL can be much higher in subpopulations, when secondary gains are expected 2 . For example the prevalence of NOHL is estimated to be 10-50% in military personnel and 9-34% in medicolegal cases of industrial workers 3 . Usually, NOHL grouped into three distinct categories: malingering, aggravation and psychogenic 4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In PHL, a discrepancy exists between the actual hearing threshold and the measured pure-tone threshold of a patient. Although experienced clinicians may easily detect PHL using conventional audiologic procedures [3] , more advanced audiologic tests have been used to diagnose PHL, including auditory brain responses (ABRs) [4] , transientevoked otoacoustic emissions (TEOAEs) [5,6] , and distortion-product otoacoustic emissions (DPOAEs) [7] . These tests have helped clinicians to diagnose PHL more accurately than before.…”
Section: Introductionmentioning
confidence: 99%